Merawat Lembang Harmonikan Marinding: Pemberdayaan Masyarakat Berdasarkan Objek Sosial, Budaya dan Agama. - Septiana, Elyza; Vira Noviana, Karisma; Izzah, Nurul; Jirana M , Nurul; Abdullah, Ramadhani; Mawansa, Akri; Syahputra Mahmud, Surya; Fajar, Muhammad (Makkareso: Riset Pengabdian Masyarakat, 2023)
The Nusantara Moderation Community Service Program in Religion is an implementation of the decision of the director general of Islamic education number 533 of 2023 concerning technical instructions for the 2023 religious moderation practical work course which was signed on January 26, 2023. Participants in the Nusantara Moderation Community Service program come from 58 religious universities throughout Indonesia. Location KKN implementation is divided into 30 posts spread across the districts of Tana Toraja and North Toraja. The method used is the ABCD approach (Asset Based Community Driven Development). That devotion carried out by posko 16 located in Lembang Marinding with the title "Caring for Lembang Harmonikan Marinding: Community Empowerment Based on Social, Cultural and Religious Objects". Based on the method used, namely the ABCD (Asset Based Community driven) approach. Development) of the program has gone through several stages. Starting from the stages of introducing social, cultural to religious assets to reflections on every aspect of the field elements which include education, social, economy and culture. Various work programs that empower the community are also part of the community service program. Among them are expo umkm gedebog fairs, moderation seminars, traditional game roadshows, reading literacy to making videos of lembang profiles.